2017
DOI: 10.14814/phy2.13084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N‐acetyl‐seryl‐asparyl‐lysyl‐proline on blood pressure, renal damage, and mortality in systemic lupus erythematosus

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease with a high prevalence of hypertension. NZBWF1 (SLE‐Hyp) mice develop hypertension that can be prevented by modulating T cells. The peptide N‐acetyl‐seryl‐aspartyl‐lysyl‐proline (Ac‐SDKP) decreases renal damage and improves renal function in a model of SLE without hypertension (MRL/lpr). However, it is not known whether Ac‐SDKP prevents hypertension in NZBWF1 mice. We hypothesized that in SLE‐Hyp, Ac‐SDKP prevents hypertension and renal damage by modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…This finding may have been due to the time course of renal injury in SLE mice; perhaps the galantamine administration was able to decrease the severity of structural and glomerular injury in tandem with decreasing blood pressure, but glomerular basement injury continued to facilitate the loss of albumin in the urine. Additionally, the female NZBWF1 model of SLE presents variably in its phenotype, and it is not unusual for several mice from a cohort to undergo fulminant renal failure or other flare-ups of the disease, similarly to human lupus patients (44); this phenomenon may help explain the lack of significance we obtained in certain areas. Our study addresses both renal inflammation and injury in the pathogenesis and maintenance of hypertension, and supports the concept that targeting a higher, neural target that regulates inflammation (e.g., the vagus nerve) may be therapeutic, even in the context of established disease.…”
Section: 5x 10mentioning
confidence: 89%
“…This finding may have been due to the time course of renal injury in SLE mice; perhaps the galantamine administration was able to decrease the severity of structural and glomerular injury in tandem with decreasing blood pressure, but glomerular basement injury continued to facilitate the loss of albumin in the urine. Additionally, the female NZBWF1 model of SLE presents variably in its phenotype, and it is not unusual for several mice from a cohort to undergo fulminant renal failure or other flare-ups of the disease, similarly to human lupus patients (44); this phenomenon may help explain the lack of significance we obtained in certain areas. Our study addresses both renal inflammation and injury in the pathogenesis and maintenance of hypertension, and supports the concept that targeting a higher, neural target that regulates inflammation (e.g., the vagus nerve) may be therapeutic, even in the context of established disease.…”
Section: 5x 10mentioning
confidence: 89%
“… 14 , 15 , 20 However, recently, we have reported that Ac-SDKP delayed the onset of hypertension in an autoimmune model of systemic lupus erythematous. 17 It is known that inflammation plays a role in blood pressure in various hypertension models, 35 , 36 and decreasing the inflammation reduces the elevated blood pressure. 35 , 37 Thus, in our study, the reduction in renal inflammation induced by Ac-SDKP could be a possible explanation for the decreased blood pressure in the HS-fed ZO rats.…”
Section: Discussionmentioning
confidence: 99%
“… 16 Recently, we have also shown that Ac-SDKP can delay the onset of hypertension in systemic lupus erythematous. 17 However, the effect of Ac-SDKP on obesity-related kidney damage and hypertension is still unknown.…”
mentioning
confidence: 99%
“…Kidney paraffin-embedded sections were stained using PAS staining and intraglomerular mesangial proliferation together with proximal tubule brush boarder alterations were analyzed [51,52]. A minimum of 50 renal fields per animal were observed using light microscope (Olympus, Germany) at final magnification of 400×.…”
Section: Methodsmentioning
confidence: 99%